2019
DOI: 10.1007/s00784-019-03025-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polymerization shrinkage of bulk-fill resin composites using microcomputed tomography

Abstract: OBJECTIVES This study evaluated the influence of cavity depth on polymerization shrinkage of bulk-fill resin composites with and without adhesive resin. MATERIALS AND METHODS Standardized box-shaped cavities (width, 4 mm; length, 5 mm, depth, 2 mm or 4 mm) were made on occlusal surfaces of extracted human third molars (N = 60). The teeth were assigned to 3 groups to receive bulk-fill resin composites (low-viscosity bulk-fill, SDR; high-viscosity bulk-fill; Filtek Bulk-Fill-FB; and TetricEvo Ceram Bulk-Fill-TB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…The superior translucency of bulk fill composites allows better light dissipation through the material (Furness et al 2014, Veloso et al 2018. Though bulk fill composite has low polymerization shrinkage, Ersen et al (2020) observed that cavity depth affects polymerization shrinkage. In the present study, the pulp chambers were standardized between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior translucency of bulk fill composites allows better light dissipation through the material (Furness et al 2014, Veloso et al 2018. Though bulk fill composite has low polymerization shrinkage, Ersen et al (2020) observed that cavity depth affects polymerization shrinkage. In the present study, the pulp chambers were standardized between groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the pulp chambers were standardized between groups. All pulp chambers had height values less than 4 mm and were statistically similar to allow effective composite polymerization and thus similar polymerization shrinkage (Furness et al 2014, Veloso et al 2018, Ersen et al 2020. All stages of root canal treatment and coronal restoration were performed on a dental mannequin, simulating clinical treatment, in order to mimic clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, most recent studies report data related to the former formulation, compatible with the bulk fill composites used in our study. 5,6,39,40 In addition, our study cannot expand on further discussion related to the potential interference of the two material composition, since they were not directly compared.…”
Section: ;28:e20190753 8/11mentioning
confidence: 99%
“… 3 , 4 Although these modifications vary, most manufacturers aim for a more translucent material with enhanced curing capability through filler modifications, 2 , 3 incorporation of high molecular weight monomers, and/or addition of new alternative photoinitiators. 2 , 5 - 8 Several commercially available bulk-fill materials have increased filler size or decreased filler content to minimize the scattering of light, thus encouraging light transmittance. 2 , 7 Moreover, modifications to monomers and photoinitiator targets improved optical properties, reduced polymerization shrinkage, and increased DOC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Nikolaidis et al reported the reinforcement of dental nanocomposite resins with different organo-modified montmorillonite nanofillers [13]. Dental materials still suffer several significant problems, such as polymerization shrinkage at the tooth-composite interface, which can lead to micro-leakage, and secondary caries [14][15][16][17][18]. In 2007, Bernardo et al [19] evaluated 1748 restorations and revealed that the use of composites increased the risk of secondary caries by about 3.5 times as compared with the use of amalgams.…”
Section: Introductionmentioning
confidence: 99%